ANALISIS OPERATIONAL EFFICIENCY RATIO DAN COST EFFICIENCY RATIO TERHADAP NET PROFIT MARGIN BANK MANDIRI TBK - Lite Lite (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research aims to examine the influence of operational efficiency ratio (OER) and cost efficiency ratio (CER) toward net profit margin (NPM) at Bank Mandiri,Tbk. The back ground of this research done is due to the bank’s low rate in obtaining NPM.Based on the classical assumption test’s result, the two independent variables chosen in this research are normally distributed with no disorder found. According to the correlationtest’s result, it is found that OER correlates to the NPM as high as 95.6% while the CER correlates to the NPM as high as 92.7%. In addition, based on the R-square test’s result, it is found that both independent variables are high as 91.6%f or each change in the NPM.Based on the F test, it is found that both independent variables ,including OER & CER have significant influence toward NPM simultaneously , in which the P-value less than 0.05 (5%).The t-test’s result, however, shows that OER has negative and effect toward NPM partially, while the CER has the positive effect and the two variables have no significant effect partially. Therefore, the step wise test is required to be done in order to get which variable that issignificant partially. And this results that OER has significant and negative effect toward NPM partially with P-value less than 0.05 (5%) and t-calculated value [-8.030] > t-table [1.860].